Association of glutamate metabotropic receptor polymorphisms and sensorineural hearing loss in adults of different age groups - Xie,Sanlin (2019)
Abstract Introduction: Sensorineural hearing loss is a common challenge all over the world, including a section of the young population. While there have been many published reports associating glutamate metabotropic receptor 7 with sensorineural hearing loss, there is no report, till date, about the association of glutamate metabotropic receptor 7 polymorphisms with sensorineural hearing loss at different ages. Objective: To test the association between the single nucleotide polymorphisms rs11928865 and rs11920109 of the glutamate metabotropic receptor 7 with sensorineural hearing loss in adults of different age groups. Methods: A total of 1661 subjects were studied. The individuals aged between 30 and 50, and between 51 and 70 years with sensorineural hearing loss comprised group A and group B, respectively. Individuals aged between 30 and 50; and between 51 and 70 years without hearing loss comprised control groups C and D, respectively. The MassARRAY method was used to analyze the genotypes. Results: The difference in genotypes for the glutamate metabotropic receptor 7 rs11928865 single nucleotide polymorphism between patients in the groups B and D was statistically significant (p = 0.018). The distribution frequencies of genotypes in patients that were aged between 30 and 50 years were not significantly different. The difference in genotypes for the rs11920109 single nucleotide polymorphism between the sensorineural hearing loss groups and control groups showed no statistical significance. Conclusion: The rs11928865 single nucleotide polymorphism was associated with the susceptibility to hearing loss in patients in group B but not with those in group A.